2007
DOI: 10.1113/jphysiol.2007.132589
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP kinase α1 subunit induces aortic vasorelaxation in mice

Abstract: Vasodilatation is a vital mechanism of systemic blood flow regulation that occurs during periods of increased energy demand. The AMP-dependent protein kinase (AMPK) is a serine/threonine kinase that is activated by conditions that increase the AMP-to-ATP ratio, such as exercise and metabolic stress. We hypothesized that AMPK could trigger vasodilatation and participate in blood flow regulation. Rings of thoracic aorta were isolated from C57Bl6 mice and mice deficient in the AMPK catalytic α1 (AMPKα1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 23 publications
4
120
3
Order By: Relevance
“…In addition, it was recently shown that smooth muscle ␣1-AMPK subunit activation induces vasorelaxation of mouse aorta independent of NO and the presence of endothelium (40), again in line with our findings. Unlike cardiac or skeletal muscles, vascular smooth muscle can maintain tonic force with low ATP turnover in the continued presence of vasoconstrictor.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, it was recently shown that smooth muscle ␣1-AMPK subunit activation induces vasorelaxation of mouse aorta independent of NO and the presence of endothelium (40), again in line with our findings. Unlike cardiac or skeletal muscles, vascular smooth muscle can maintain tonic force with low ATP turnover in the continued presence of vasoconstrictor.…”
Section: Discussionsupporting
confidence: 81%
“…AMPK activity can be regulated by a low energy state (increases in the AMP/ATP ratio), phosphorylation of Thr 172 and Ser 485/491 of the α subunit, and stresses such as reactive oxygen species (ROS), hypoxia, and genotoxic drugs (Stein et al, 2000;Hawley et al, 2003;Hurley et al, 2006). AMPK has various cellular functions, including the regulation of cellular metabolism, ion channels, and gene expression (Hardie, 2004), activation of glucose transport during hypoxia and ischemia via eNOS phosphorylation (Li et al, 2004), cell cycle arrest via p53 phosphorylation (Jones et al, 2005), differentiation of endothelial progenitor cells via eNOS activation (Li et al, 2008), inhibition of protein synthesis via TSC1/2, induction of aortic vasorelaxation in mice (Goirand et al, 2007), and regulation of apoptotic cell death signals (Cao et al, 2008;Kim et al, 2008;Lee et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…21 AMPK activation causes the NO-mediated relaxation in the spontaneously hypertensive rats. [25][26][27][28] AMPK, at the same time, causes the endothelium independent vascular smooth muscle relaxation in the aort preparations of the Mouse. 27 …”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 99%
“…It therefore shows a vasoprotective effect. [25][26][27] It is thought that the vasoprotective effects of the therapeutic agents like, metformin 24 , thiazolidinediones and statins also occur via the AMPK activation. 21 AMPK activation causes the NO-mediated relaxation in the spontaneously hypertensive rats.…”
Section: Adenosine Monophosphate-activated Protein Kinase Pathwaymentioning
confidence: 99%
See 1 more Smart Citation